Letter of Credit (L/C) dalam Produk Bank Syariah - Khoiruddin, Khoiruddin (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2010)
The existence of letter of credit which is really accordance with Islamicsyariah principles has been waited by moslem bussinessmen who want torun their religion values in all their life. The conventional L/C is consideredas on syariah L/C due to its practice still applicates the interest system. Theregulation of L/C Syariah has been existed in Act No. 21/2008 concerningPerbankan Syariah, in article 19 p, and long before the act was made, theexistence of L/C Syariah has been mentioned in Fatwa Dewan SyariahNasional MUI NO.34/DSN-MUI/IX/2002 concerning L/C Impor Syariah andFatwa Dewan Syariah Nasional MUI No. 35/DSN-MUI/IX/2002 concerningL/C Ekspor Syariah. L/C Syariah can applicate some models of akads/contracts, such as: wakalah bi al-ujrah, qard, murabahah, salam/istisna’,mudarabah, musharakah, hawalah and al-bai’. From the variety of contractmodels which can be applicated to the L/C Syariah, wakalah bi al-ujrah andmurabahah are considered as the most efficient, safest, and the most minimumrisky. Wakalah bi al-ujrah and murabahah are also an agreement that closestto the goal of L/C existence, that is: makes the international trade processbecome easier